Multi-metal tolerance efficiency and bioremediation capabilities of Bacillus aerius from mangrove rhizosphere - Surabhi, Awasthi; Sundaramanickam, Arumugam; Barathan, Velayutham; Praveena, Sarva Mangala (Taylor and Francis, 2025)
Bioremediation is an effective and eco-friendly way to remove heavy metal contamination in the environment. The current study intends to isolate, identify, and characterize bacteria from soil samples, and assess their efficiency in degrading heavy metals (Copper, Chromium, and Zinc) under batch conditions. In the initial screening, 27 bacterial strains were selected out of 27 isolates, one strain GC6 showed the highest tolerance to heavy metals, which showed Cupper and Chromium resistance at 5000 ppm concentrations, after 24 h of incubation. The 16S rRNA phylogenetic association was resolute using bioinformatics and this bacterial strain GC6 as Bacillus aerius with 100% sequence resemblance. The strain B. aerius GC6 was utilized to remediate multi-heavy metal concentrations at in-situ conditions. The concentrations of heavy metals in broth cultures were analyzed using atomic absorption spectroscopy (AAS). The strain GC6 showed biosorption capabilities, with removal efficiencies of 58.3% for Cu2+, 80.1% for Cr6+, and 94.4% for Zn2+ at a concentration of 500 ppm. The study suggests that B. aerius GC6 can efficiently remove heavy metals and these bacteria could be used for bioremediation applications in environments contaminated with heavy metals.